1278 Outcome Following Fetal Pleuroamniotic Shunting in 114 Large Hydrothoraces. (October 2012) - Kelly, E; Seaward, G; Windrim, R; Ryan, G
Abstract : Introduction: Untreated, fetal hydrothorax is associated with significant morbidity and a mortality rate of approximately 80–90%. Population: 114 fetuses with isolated large pleural effusions underwent pleuroamniotic shunting at our perinatal centre. All had an extensive antenatal work-up including: detailed anatomy, echocardiogram, karyotype, infectious testing for CMV, Toxoplasmosis and Parvovirus. 84 were bilateral, 72 (63%) were hydropic and 41 (36%) had associated polyhydramnios, . Mean maternal age was 30.2 years, the mean gestation at diagnosis was 25 weeks and at shunting 27.6 weeks. 64 required bilateral shunts and, of unilateral, 27 were left-sided and 23 right-sided. 25 underwent simultaneous amnioreduction. The mean interval to delivery was 7 wks. Results: There were 15 (12.3%) intrauterine deaths. 26 (23%) neonatal deaths and 73 (64.7%) survivors. Additional abnormalities including genetic, metabolic and neurological syndromes were identified antenatally in 8 cases and postnatally in 9. Of 99 liveborn babies, 76 (77%) delivered at our perinatal centre. Postnatally, 46 required ventilation, 38 (50%) required chest tubes, of whom 19 (26%) died. Of 73 survivors, 2 (3%) were lost to follow-up, 4 (5.5%) are < 4 months of age, 10 (14%) showed evidence of significant developmental delay, including 3 with Trisomy 21, and 1 had mild developmental delay. Fifty five (75%) are developing normally. Conclusion: Fetal hydrothorax can be associated with a wide range of conditions, some of which may not be detectable antenatally. Fetal therapy significantly improves perinatal outcome, although mortality remains high. On long term follow up, approximately 75% of survivors are developmentally normal.